2018
DOI: 10.1097/rti.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Technological Advancements in Echocardiographic Assessment of Thoracic Aortic Dilatation

Abstract: In patients with aortic dilatation or aneurysm, new techniques (mainly 2D-3D probes allowing XP views) facilitate accuracy of aortic measurements at different sites of the vessel and allow standardization of analysis to better compare with MDCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Most studies comparing 2-dimensional TTE with CT and MRI found that TTE significantly underestimates aortic root diameters compared with CT [162][163][164] and MRI, [163][164][165][166] likely related to off-axis image acquisition and root asymmetry. On the other hand, 3D TTE correlates well with CT. 165 Several studies also have demonstrated that abdominal ultrasound systematically underestimates the size of abdominal aortic aneurysms by ≈1 to 3 mm compared with CT. [167][168][169][170][171] In the nondissected thoracic and abdominal aorta, the agreement between diameter measurements obtained with CTA and MRA is good when the same analysis technique is used, [168][169][170][171] and interobserver agreement is excellent. 163,164,172 No such data are available for chronically dissected distal aortic segments, however.…”
Section: Differences Within and Between Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies comparing 2-dimensional TTE with CT and MRI found that TTE significantly underestimates aortic root diameters compared with CT [162][163][164] and MRI, [163][164][165][166] likely related to off-axis image acquisition and root asymmetry. On the other hand, 3D TTE correlates well with CT. 165 Several studies also have demonstrated that abdominal ultrasound systematically underestimates the size of abdominal aortic aneurysms by ≈1 to 3 mm compared with CT. [167][168][169][170][171] In the nondissected thoracic and abdominal aorta, the agreement between diameter measurements obtained with CTA and MRA is good when the same analysis technique is used, [168][169][170][171] and interobserver agreement is excellent. 163,164,172 No such data are available for chronically dissected distal aortic segments, however.…”
Section: Differences Within and Between Imaging Modalitiesmentioning
confidence: 99%
“…Most studies comparing 2-dimensional TTE with CT and MRI found that TTE significantly underestimates aortic root diameters compared with CT 162–164 and MRI, 163–166 likely related to off-axis image acquisition and root asymmetry. On the other hand, 3D TTE correlates well with CT. 165 Several studies also have demonstrated that abdominal ultrasound systematically underestimates the size of abdominal aortic aneurysms by ≈1 to 3 mm compared with CT. 167–171…”
Section: Measurement Principlesmentioning
confidence: 99%